Agile Leadership Behaviors and Their Role in Promoting Workplace Spirituality : An Analytical Study of The Prespectives of a Sample of Lecturers at Knowledge University - Erbil - Daroon Faridun Abdulla; Pirshing Salih Al Askari; Zana Majed Sadq (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study aims to identify the role of agile leadership behavior in its dimensions (humility, confidence, objectivity, patience, calmness, wisdom) in promoting workplace spirituality, represented by (purposeful work, values alignment, sense of belonging, job integration) at Knowledge University. After reviewing a group of studies and literature, theoretical concepts were written and a model and hypotheses were built based on agile leadership behaviors and workplace spirituality. In order to collect data, a questionnaire form was relied upon, which was distributed randomly to the study sample represented by the teaching staff at Knowledge University, which numbered (57) teaching staff and at rates (43.8%) from the study population, which consisted of (130) individuals. The reliability (Cronbach’s alpha coefficient) was performed to verify its stability and reliability and to ensure its validity in measuring variables, in addition to extracting the frequency distributions and arithmetic mean of the paragraphs of the questionnaire through the use of (SPSS v25) program. In order to measure the strength of the correlation and regression relationships between the research variables, I used simple correlation analysis and simple linear regression. The results showed the existence of a correlation and effect between the variables and their dimensions. Based on the results, a number of recommendations were made regarding the need for administrative leaderships at Knowledge University to focus on their following agile leadership behaviors in order to enhance workplace spirituality.